JANE HIRSHFIELD’S MY LIFE WAS THE SIZE OF MY LIFE: MORPHO-SYNTACTIC STRUCTURATION - Priscilla F. Canoy; Nathaniel G. Gido; Thalia A. Edoloverio (Galaxy International Interdisciplinary Research Journal, 2022)
Using morphemic structure, tree diagramming, and immediate constitute analysis, including phrase structuration, to examine Jane Hirshfield's representative poem. Through textual analysis, the study investigates morphemic structure, phrase structuration, and instantaneous constitute analysis. Almost all of the terms in the study had plural suffixes, followed by verb suffixes, particularly in the past tense form of a word or term and gerund –ing. Comparative adjectives are also given the suffix –er. Almost every word has a plural suffix, which is followed by verb suffixes, particularly in the past tense form of a word or term and gerund –ing. Comparative adjectives are also given the suffix –er. Because there are more nouns and pronouns used in the noun phrase, it is more dominant. The poem is made up of fifteen idealized sentences, the majority of which are noun and verb phrases, followed by prepositional phrases, adjectival phrases, and adverbial phrases. Because such descriptions are not required to explain the thoughts, the poet may use less adjectives and modifiers in the poem. It is noticeable that the poet uses simple language and word choices in the poem in order for the listener to understand it more easily.